The characteristics of social information processing demonstrated by murderers and persons convicted for other offences - VALICKAS, GINTAUTAS; VANAGAITĖ, KRISTINA; NAVICKAS, VYTAUTAS (Kriminologijos studijos, 2014)
The study purpose is to compare the characteristics of social information processing demonstrated by adult male offenders convicted for different offences and adult males against whom not a single action has ever been brought. The study involved 131males: 98 convicts (who had committed non-violent, violent / mixed-type offences and murder / mixed-type offences), and 33 control group participants. In order to explore the characteristics of social information processing, the methodology of ambiguous interpersonal interaction situations and the structural interview method was used. Inquiry was performed individually, lasting up to 45 minutes per each participant. The findings showed that convicts, compared to the control group participants, recalled in their accounts of the observed situation a considerably smaller number of significant details (p < 0,001), providing considerably more subjective interpretations of these details (p < 0,01), demonstrating a much higher mean of possible reactions available to the protagonist (p < 0,05), and appraising the protagonist’s pro-social response as proper far less frequently (p ≤ 0,05). Persons convicted for murder / mixed-type offences, in comparison with the ones convicted for non-violent and violent / mixedtype offences, used to describe the protagonist’s feelings as neutral considerably less frequently, describing it as “positive and hostile” much more often (p < 0,05), also, theythought more often that the protagonist would fail to put into practice his response option (p < 0,05).The worked out multinomial logistic regression model showed that protagonist’s aims and thoughts may help to forecast the choice of a hostile response: hostile thoughts emerging in a definite situation may encourage the choice and implementationof hostile responses; similarly, hostile aims may prompt the choice and implementation of hostile and neutral (but not pro-social) responses.So, the findings indicate that: 1) convicts, compared to persons against whom not a single action has ever been brought, process social information in ambiguous situations in a more tendentious way; 2) adult males convicted for various offencesprocess social information in ambiguous situations more or less differently. Further inquiry is needed in order to confirm these tendencies.Key words: persons convicted for different offences, ambiguous social situations, social information processing.